Incidence and long-term outcome of severe asthma-COPD overlap compared to asthma and COPD alone: a 35-year prospective study of 57,053 middle-aged adults - Baarnes, Camilla Boslev; Andersen, Zorana Jovanovic; Tjønneland, Anne; Ulrik, Charlotte Suppli (International journal of chronic obstructive pulmonary disease, 2017)
Incidence and prognosis for severe asthma-COPD overlap is poorly characterized. We investigated incidence and long-term outcome for patients with asthma-COPD overlap compared to asthma and COPD alone. A total of 57,053 adults (aged 50-64 years) enrolled in the Danish Diet, Cancer, and Health cohort (1993-1997) were followed in the National Patients Registry for admissions for asthma (DJ45-46) and COPD (DJ40-44) and vital status. Asthma-COPD overlap was defined as at least one hospital admission for asthma and one for COPD (different time points), and incident asthma-COPD overlap as at least one of the diagnoses occurring after enrollment into the Diet, Cancer, and Health cohort. A total of 1,845 (3.2%) and 4,037 (7.1%) participants had admissions for asthma and COPD, respectively, with 662 (1.2%) participants with asthma-COPD overlap. Incidence rate of asthma-COPD overlap per 1,000 person-years was higher in women (0.73) than in men (0.54) ( <0.02). Mortality rate was higher in asthma-COPD overlap (25.9 per 1,000 person-years) compared with COPD (23.1, <0.05) and asthma (7.9, <0.001) alone. Compared to COPD alone, mortality was higher in women with asthma-COPD overlap (19.6 and 25.5, respectively; <0.01), and the excess mortality rate for asthma-COPD overlap patients was most prominent for younger age groups (12.9 compared to 7.2 and 4.6 for COPD and asthma alone, respectively; <0.01). This large population-based study revealed a higher incidence of severe asthma-COPD overlap in women compared to men, and furthermore that all-cause mortality is higher in women and younger subjects with asthma-COPD overlap compared with those with asthma or COPD alone.